Longitudinal data from a school-based intervention - The ACORDA project (Datos longitudinales de un programa intervención en la escuela - proyecto ACORDA) - Luísa Aires; Gustavo Silva; Ana Inês Alves; Ana Filipa Medeiros; Henrique Nascimento; Clarisse Magalhães; Clarice Martins; Petronila Rocha Pereira; Alice Santos-Silva; Luis Belo; Jorge Mota (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2015)
Abstract. The aim of this study was to analyse changes over 8-months of a multidisciplinary school-based intervention program (ACORDA-Project), in body fat, metabolic profile and physical activity (PA). 40 children [22 girls (55%), and 18 boys age=8.4±1.2] of 6 schools participated in a multidisciplinary program during a school year. Blood pressure (BP), physical activity (PA) by accelerometers, percentage of body fat (%BF) and of trunk fat (%TF) by DXA, and plasmatic total cholesterol (TC), triglycerides, HDL-cholesterol, LDL-cholesterol, insulin and glucose were taken at the baseline (Time point 1, TP1) and at the end of the intervention (Time point 2, TP2). General Linear Models (Repeated Measures Analysis of Covariance) was carried out comparing values at baseline vs. final evaluation, with adjustments for gender and age at baseline. Further adjustments were made to relative changes (increase%X) in height, weight, total PA through steps.day-1, sedentary (SEDPA), light (LIGPA) and moderate to vigorous (MVPA) intensities. Relative changes were calculated as: increase%X = (Xfinal – Xbaseline) / Xbaseline. Statistical significance was set at 5%. Eta squared (n2) was used as an indicator of effect size. There was a significant increase of LIGPA and MVPA, (P<0.05), and significant reduction in systolic blood pressure (P<0.05), but not in diastolic blood pressure. For TC and fasting glucose, significant reductions were also found P<0.05). No changes were observed for other traditional cardiovascular risk factors. The present study found that 8-months of multidisciplinary intervention provided a significant increase in PA levels and reduced cardiovascular risk factors in school children, highlighting the importance of this type of intervention through promotion of PA and the positive impact on children health.